Measurement of an elliptic jet - Muhammad Shukur Mohamad Ayub. (2009)
This project focuses on the experimental study of an elliptic jet of aspect ratio 2:1. The axes dimensions of the jet are as follows: 50 mm and 25 mm for the major and minor axes respectively. The scope of this project encompasses the initial flow conditions, the velocity profiles of the various flow regions, self-preservation and the phenomenon of axis switching in the elliptic jet. Data collated were obtained from various streamwise locations of two typical probes; single as well as cross-wire probes. The velocity hereafter termed as the jet exit velocity were set as 25.0 +/- 0.5 m/s. The calculated parameters for the experiment are as follows; equivalent diameter, De to be 0.0246 m and the Reynolds number to be 44528. The experiments were divided into two parts, namely the single wire experiments followed by the X-wire experiments. For the former sections, velocity values were obtained in the transverse and spanwise direction along the streamwise distances. It was observed that the potential core ends at ~ 7 De. The interaction region occurs between ~ 7 to 10 De. Thereafter, it was observed that the flow became self-preserved between 10 to 15 De. The occurrence of axis switching was approximately observed at 2 distinct locations: 6.8 De, and 11.2De. For the subsequent part of the experiment, it was deduced that the potential core ends approximately at 7 De for crosswire measurements. Self-similarity in mixing layer was observed to occur at 4 De for the minor and major axes respectively. The normalized Reynolds normal stress u’ reached self-preservation at 20 De while for w’ and v’, the results did not show signs of self-preservation. For the normalized Reynolds shear stress, it was observed that self-preservation was not reached till 20 De. The peak values were observed at 0.006 and 0.005 for the minor and major plane respectively. The normalized axial turbulent intensities reached a peak value of 0.2 while the lateral turbulent intensities showed gradual increase without converging to a value for distances from 1 to 20 De. The occurrence of axis switching for the crosswire measurements were observed at approximately 7 and 11.6 De. The spreading rates obtained from the crosswire measurement indicate 0.0822 and 0.0946 for the minor and major axes. The geometric virtual origins were also evaluated to be 0.802 and 0.59 for the respective axes. Lastly, the decay rates were calculated to 0.08167 and 0.081857 for the minor and major axes respectively. The kinematics virtual origins were found to be 0.55 and 0.567 respectively.